XML Binding Frameworks in the Context of Service-Oriented Architecture Make an informed choice about a binding framework for your SOA needs. - Majumdar, Bijoy
This article critically evaluates the role of XML binding frameworks play in the context of service oriented architecture (SOA) platforms, and it also provides an objective evaluation of the popular XML binding frameworks in a J2EE environment.